Prebiotic Wheat Bran Fractions Induce Specific Microbiota Changes - D’hoe, Kevin; Conterno, Lorenza; Fava, Francesca; Falony, Gwen; Vieira-Silva, Sara; Vermeiren, Joan; Tuohy, Kieran; Raes, Jeroen (Frontiers in Microbiology, 2018)
Wheat bran fibers are considered beneficial to human health through their impact on gut microbiota composition and activity. Here, we assessed the prebiotic potential of selected bran fractions by performing a series of fecal slurry anaerobic fermentation experiments using aleurone as well as total, ultrafine, and soluble wheat bran as carbon sources. By combining amplicon-based community profiling with a fluorescent in situ hybridization (FISH) approach, we found that fecal fermentation of several wheat fractions favors the growth of Proteobacteria such as Escherichia and Bilophila. These effects were encountered in all but one (total wheat bran) fermentation experiments. Growth of Bifidobacterium species was stimulated after fermentation using ultrafine, soluble, and total wheat bran, in the latter two as part of a general increase in bacterial load. Both ultrafine and soluble wheat bran fermentation resulted in a trade-off between Bifidobacterium and Bilophila, as previously observed in human dietary supplementation studies looking at the effect of inulin-type fructans on the human gut microbiota. Aleurone selectively stimulated growth of Dorea and butyrate-producing Roseburia. All fermentation experiments induced enhanced gas production; increased butyrate concentrations were only observed following soluble bran incubation. Our results open perspectives for the development of aleurone as a complementary prebiotic selectively targeting colon butyrate producers.